PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MODEL PENEMUAN TERBIMBING UNTUK MELATIHKAN KETERAMPILAN PROSES SAINS PADA MATERI POKOK SUHU DAN KALOR - Sri Martini; ZA Imam Supardi; Rudiana Agustini (Universitas Negeri Surabaya, 2017)
The research consist of two steps. The first step discusses about the development of physics teaching and learning materials of guided discovery model, in order to practice science process skills by adapting 4-D model. The second focuses on the implementation of the physics learning set developed by using one group pretest-posttest research design.It is done to 32 students on X C of SMAN 1 Pamekasan 2012/2013 which concern on the main topic Temperature and Heat, by four observers and without replication. The developed materials set is lesson plan (RPP), worksheets (LKS), students book, and form of assesment validated by three experts (validator). Those are categorized œgood and visiable to be used in the teaching-learning process. The result of this research is analized descriptively, namely: (1)the lesson plan (RPP)implementation is categorized œgood with implemented persentage 92,25%, (2)the most dominant of students learning activity is doing discovery activity to practice the students science process skills that is 32,91%, (3)the improvement of students science process skills through the result of 8 aspects observationclassically, (4)the result of students learning on THB product, science process skills, and psycomotoric individually have improvement and its classically categorized œcomplete, (5) students response positively and anthusiastically toward guided learning discovery in order to practice science process skills, and (6) the obstacles found on this field, students are not familiar with guided learning discovery model and doing scientific research to practice science process skill, so that the use of time often is not suitable with the lesson plan (RPP) due to the new discoveries that must be explanned to the students. Penelitian ini dilaksanakan dalam dua tahap. Tahap pertama mengembangkan perangkat pembelajaran fisika model penemuan terbimbing untuk melatihkan keterampilan proses sains dengan mengadaptasi model 4-D. Tahap kedua adalah implementasi perangkat pembelajaran fisika yang dikembangkan dengan menggunakan desain penelitian one group pretest-posttest design. Peneltian ini dilakukan di SMAN 1 Pamekasan dengam sampel 32 orang siswa kelas X C tahun pelajaran 2012/2013 pada materi pokok suhu dan kalor, dengan empat orang pengamat tanpa replikasi. Perangkat yang dikembangkan berupa RPP, LKS, Buku Ajar Siswa, dan Lembar Penilaian telah divalidasi oleh tiga pakar (validator) dengan kategori baik dan layak digunakan dalam pembelajaran. Hasil yang diperoleh dalam penelitian ini dianalisis secara deskriptif diantaranya, (1) keterlaksanaan RPP dikategorikan baik, dengan persentase keterlaksanaan 92,25%, (2) aktivitas siswa dalam pembelajaran yang paling dominan adalah melakukan kegiatan penemuan untuk melatihkan keterampilan proses sains siswa sebesar 32,91%, (3) hasil pengamatan 8 aspek keterampilan proses sains siswa secara klasikal meningkat, (4) hasil belajar siswa pada THB produk, keterampilan proses sains maupun psikomotor secara individu meningkat dan secara klasikal dikategorikan tuntas, (5) respon siswa positif dan antusias terhadap pembelajaran penemuan terbimbing untuk melatihkan keterampilan proses sains siswa, dan (6) kendala/hambatan yang ditemukan di lapangan, siswa masih belum terbiasa dengan pembelajaran penemuan terbimbing, dan melakukan penyelidikan ilmiah untuk melatihkan keterampilan proses sains, sehingga penggunaan waktu kadang kurang sesuai dengan RPP karena banyak hal baru yang perlu dijelaskan pada siswa.